EVALUATION OF IMPLEMENTING FINANCIAL SERVICES AUTHORITY AS A TAX SUBJECT - Ario Narabewa; Yohanes Yohanes (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
This researchis conducted to examine the determination of Otoritas Jasa Keuangan as a tax subject and object by the Directorate General of Taxes. DGT determines levies by the OJK on the financial sector related to tax objects. This can lead to double taxation problem depending on the remaining levies of the current year and the following year's budget must be submitted by the OJK to the Treasury. This study employs the state sovereignty theory to request that this stipulation is under statutory regulations. Case study is chosen as the research strategy to deepen the study of this determination phenomenon more deeply and can provide advice to OJK and the Directorate General of Taxes. The data were collected by interview method and document study. The result of this study found that the OJK as an entity has the function to conduct pure administrative tasks.Theresult of this translation shows that OJK’s levy is part of PNBP, thus it cannot be used using object tax